SAT0185 Certolizumab pegol serum levels ≥20 mg/l are associated with improvement in das28 in rheumatoid arthritis patients. data from the nor-dmard study. (12th June 2018) - Gehin, J. E.; Syversen, S. W.; Warren, D. J.; Goll, G. L.; Sexton, J.; Strand, E. K.; Kvien, T. K.; Bolstad, N.; Lie, E.
Abstract : Background: Measurement of serum drug levels can help clinicians tailor treatment with TNF-inhibitors. An association between certolizumab pegol (CP) serum levels and treatment response in rheumatoid arthritis (RA) patients (pts) has previously been demonstrated in a prospective observational study (1). These results need to be confirmed in other studies, with particular focus on finding an optimal therapeutic serum level for CP. Objectives: To examine the association between serum CP drug levels and treatment response in RA pts and to identify a therapeutic target level. Methods: Patients with a clinical diagnosis of RA starting standard treatment with CP included in the NOR-DMARD registry with biobank sample at 3 months follow-up, were included in the present analyses. Serum drug levels (non-trough) were analysed with an in-house immunofluorometric assay automated on the AutoDELFIA immunoassay platform. We studied association between serum CP level and &x25B3;DAS28 and EULAR good/moderate response at 3 months by multivariable linear and logistic regression analyses, respectively, adjusting for age, sex and prior bDMARD (Y/N). Results: In 91 included patients, median serum drug level at 3 months follow up was 34.7 mg/L (17.6–44.6). Response data were available in 81/91 patients. Serum CP level ≥20 mg/L was associated with greater improvement in DAS28 at 3 months (β=0.89 (95% CI 0.03–1.74), P=0.04. 44.4 % of pts with CP level <20 mg/L achieved EULAR response after 3 months treatment, while 73.5 % of pts with CP level 20–40 mg/L and 55.2 % with ≥40 mg/L were responders. However, the difference in EULAR response between pts with CP level ≥20 vs. <20 mg/L did not reach statistical significance (OR 1.5 (95% CI 0.5–5.1), P=0.48). Conclusions: Certolizumab serum levels ≥20 mg/L were associated with DAS28 improvement, but not significantly with EULAR response after 3 months treatment in RA pts. We suggest 20 mg/L as a lower target limit for non-trough CP samples in RA-patients. No additional benefit of having a certolizumab level over 40 mg/L was observed. Reference: [1]Jani M, et al. AnnRheum Dis2017;76(1):208–13. Disclosure of Interest: J. E. Gehin Consultant for: Roche, S. Syversen Consultant for: Roche, D. Warren: None declared, G. Goll Consultant for: Abbvie, Biogen, Boehringer Ingelheim, Orion Pharma, Eli Lilly, Novartis, Pfizer, MSD, Roche, UCB, J. Sexton: None declared, E. Strand Consultant for: Pfizer, T. Kvien Consultant for: AbbVie, Biogen, BMS, Boehringer Ingelheim, Celgene, Celltrion, Eli Lilly, Epirus, Hospira, Merck-Serono, MSD, Mundipharma, Novartis, Oktal, Orion Pharma, Hospira/Pfizer, Roche, Sandoz, UCB, N. Bolstad Consultant for: Pfizer, Orion Pharma, Napp pharmaceuticals, Takeda, Roche, E. Lie: None declared